The management of dental fracture on tooth 61 in a child with attention deficit hyperactivity disorders - Veranica Veranica; Mochamad Fahlevi Rizal (Universitas Airlangga, 2010)
Background: Attention deficit hyperactivity disorder (ADHD) is often characterized as a neurobehavioral developmental disorder, impaired concentration, impaired motor skills, impulsivity, and hyperactivity, and also diagnosed as psychiatric disorders. Children with ADHD would have a tendency of the traumatized anterior teeth because of their hyperactive behavior. Dental trauma is actually one of factors causing the damages of the deciduous teeth and the permanent teeth. Dental and mouth care for children with special needs, such as children with ADHD, requires special treatment. Purpose: This study is aimed to report the case management of the dental fracture of the tooth 61 in a child with ADHD. Case: A four-year old girl suffered from both ADHD and dental fracture involving the dentin of the tooth 61. Case management: The examination of the patient with dental fracture consists of emergency examination and further investigation. The emergency examination covers general condition and clinical situation. Based on the dental radiographic assessment, it is known that the dental fracture of the tooth 61 had involved the dentine, the resorption had reached 1/3 of the apical teeth and the permanent teeth had been formed. The application of calcium hydroxide on the opened dentin is aimed to improve the formation of the secondary dentin served as pulp protector. Next, the restoration of the traumatized teeth used compomer since it does not only meet all the aesthetic requirements, but it also releases fluoride. Management of the patient's behavior with ADHD was conducted by non-pharmacological method; tell show do (TSD) method combined with restrain method. Conclusion: It can be concluded that the application of calcium hydroxide and the restoration of the teeth with compomer could provide maximum results through the combination of TSD and restrain methods that can effectively increase the positive value to replace the negative behaviors that have been formed. Latar belakang: <span style="font-family: Tribune-Italic; font-size: 9pt;